Diaspora Remittance and Enterprise Creation: The Nigerian Context - Idowu Emmanuel OLUBODUN; Emmanuel Abiodun OLAWUMI (Management and Economics Review)
The impact of diaspora remittances to any economy has become an imperative such that its contribution is highly desired. This study examines the relationship between diaspora remittance and enterprise creation in Nigeria while controlling for GDP Per Capita, political stability, and exposure to entrepreneurship education. The study employs ex-post facto research design using data from the World Bank Database covering 17 years (2006-2022). The descriptive analysis explains the trend and pattern of the connection between diaspora remittance and enterprise creation, while regression technique ascertains the influence. The trend and pattern between diaspora remittance and enterprise creation shows that both exhibit overall parallel upward trends except in the year 2020-2022 where enterprise created exceeded inflow of remittances. Diaspora remittance does not have significant effect on enterprise creation in Nigeria. The study reveals that, to spur enterprise creation in Nigeria, remittances may be not sufficient. The study concludes that an improvement in business environment, provision of entrepreneurial education and training, and stable political atmosphere will be necessary to engender the impact of remittances on enterprise creation. Further studies can focus on other West Africa countries.